2015
DOI: 10.1016/j.ajic.2015.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Spread of infectious microbes during emergency medical response

Abstract: Results suggest firefighters' hands were the main vehicles of microbial transfer. Current practices were not consistently applied or standardized and minimally reduced prevalence and quantity of microbial contamination on EMS surfaces. Although use of a consistent protocol of H2O2 wipes significantly reduced percent prevalence and concentration of viruses, training and promotion of surface disinfection should be provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 33 publications
1
28
0
Order By: Relevance
“…To determine the best collection, processing, and results representation approach, three sampling approaches Additionally, coliphage MS2 (ATCC 15597-B1; American Type Culture Collection, Manassas, VA) was used to seed the same three canals (one experiment per canal) to serve as a microbial tracer organism. This non-pathogenic virus has been used as a surrogate for many pathogens in various environments (Reynolds et al, 2015;Sinclair et al, 2009;Valdez et al, 2015). Coliphage samples were serially diluted with sterile phosphate-buffered saline (PBS; pH 7.4; Sigma-Aldrich, St. Louis, MO) to create 10, 1, -1 , 10 -2 , 10 -3 , and -4 ml duplicate subsamples.…”
Section: Field Analysis and Sample Collectionmentioning
confidence: 99%
“…To determine the best collection, processing, and results representation approach, three sampling approaches Additionally, coliphage MS2 (ATCC 15597-B1; American Type Culture Collection, Manassas, VA) was used to seed the same three canals (one experiment per canal) to serve as a microbial tracer organism. This non-pathogenic virus has been used as a surrogate for many pathogens in various environments (Reynolds et al, 2015;Sinclair et al, 2009;Valdez et al, 2015). Coliphage samples were serially diluted with sterile phosphate-buffered saline (PBS; pH 7.4; Sigma-Aldrich, St. Louis, MO) to create 10, 1, -1 , 10 -2 , 10 -3 , and -4 ml duplicate subsamples.…”
Section: Field Analysis and Sample Collectionmentioning
confidence: 99%
“…The ambulances are non-static environments that must be ready for service shortly after delivering the patient to the emergency department, hence offering limited time and equipment to clean and decontaminate [ 7 ]. In addition to logistic challenges, studies indicate that implementation of cleaning measures [ 7 , 8 ] and efficiency of cleaning [ 9 ] within the EMS vary. Moreover, pathogens have been found in both the ambulances [ 6 , 7 , 10 ], on uniforms [ 11 , 12 ] and on the hands of the providers [ 13 ], and the spread of microbes within the ambulance environment is a proven reality [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rago et al (5) found S. aureus in 69% (49/71) of ambulances serving a metropolitan area; 77% (77/100) of the isolates were resistant to at least one antibiotic, and 34% (34/100) were resistant to two or more antibiotics. Valdez et al (6) seeded two high-contact surfaces with a bacteriophage and found that the contamination was spread to 56% (27/48) of other commonly-touched surfaces that were examined, primarily by hand contact. Standard cleaning practices only partly reduced the contamination.…”
Section: Introductionmentioning
confidence: 99%